Ad Hoc Network Simulators Features - Filiposka, Sonja; Trendafilova, I; Trajanov, Dimitar; Grnarov, Aksenti (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2003)
The deployment of wireless applications or protocols in the context of MANETs, often requires stepping through a simulation phase. There are several popular simulators, such as OPNET Modeller, GloMoSim or NS-2. Since NS-2 is more frequently used in worldwide network societies we present our experiences gained with the use of NS-2 for simulations of wireless mobile ad hoc networks. Facing the problem of poor documentation for ad hoc networks, our research resulted in reach documentation for NS-2 trace files and behaviour of ad hoc networks. We observed the flexibility of NS-2 simulator, by the means of adding new application layers, change of existing routing protocols, and incorporating various extensions created outside the NS-2 development team.
Keywords: Mobile Ad-hoc networks, simulations, network simulators